Influence of grain sorghum planting dates and Palmer amaranth emergence timings on competitive outcomes - Gastler, Lindsey K. (Kansas State University, 2020)
Grain sorghum (Sorghum bicolor L.) is an important crop to Kansas agriculture, and Palmer amaranth (Amaranthus palmeri S. Wats.) is considered the most troublesome weed in grain sorghum. In 2019, field experiments were conducted near Manhattan and Hutchinson, Kansas to determine the influence of grain sorghum planting dates and Palmer amaranth emergence timings on competitive outcomes. Grain sorghum was planted on June 3 and July 1 at Manhattan and May 17 and June 17 at Hutchinson. Natural populations of Palmer amaranth were established at an early and late emergence timing relative to crop planting along with a weed-free treatment. Palmer amaranth was thinned and maintained at a target population of 4 plants m⁻¹ of row. The growth stage and height of grain sorghum and Palmer amaranth were recorded weekly. Biweekly up to grain sorghum flag-leaf stage, two grain sorghum and two Palmer amaranth plants plot⁻¹ were harvested to measure leaf area and biomass. Grain sorghum was harvested to measure yield and seed weight. Late planted grain sorghum accumulated height, leaf area, and biomass more quickly than early planted grain sorghum on a time scale of days after planting (DAP) at both locations. On a scale of growing degree units (GDU), grain sorghum leaf area and biomass accumulation at Manhattan were similar across planting dates, while the late planting accumulated more height. In Hutchinson, grain sorghum leaf area accumulation was similar across plantings, while the late planting accumulated height and biomass more quickly on a GDU scale. Palmer amaranth density in both sites were less than desired and inconsistent, therefore, it was impossible to test the effects of Palmer amaranth emergence timing. In Manhattan, grain yields were similar across treatments, excluding the treatment with the highest Palmer amaranth density (1.5 plants m⁻¹ of row), and seed weight was greater in the early planting than the late. In Hutchinson, grain sorghum yield was 37% less in the early planting than the late planting, due to poor crop establishment in cool soil temperatures after planting, and poor pollination and grain fill during hot and dry conditions. Later planted grain sorghum grew faster than early planted grain sorghum, thus was more competitive against weed competition in early growth stages. This research demonstrated a potential tactic that a producer could implement to enhance early season competitiveness of grain sorghum against Palmer amaranth.
Keywords: Palmer amaranth; grain sorghum; planting date; emergence